PROBLEMATIKA PEMILIHAN UMUM KEPALA DAERAH (PEMILUKADA) DI SURAKARTA TAHUN 2010 - Widada, Sutapa Mulja (PARENTAL, 2013)
The results of research show that the regional election in Surakarta Year 2010 can run smoothly with parameters: administrative electoral success, political success and the electoral success of quality products. Nevertheless, there is still the problem of including the establishment Supervisory Committee, the organizing body Formation (PPK, PPS, and KPPS), budget Election, Data and Designation Update Voters List (DP4), Campaign, Regional Head General Election Regulations. Election classic problem of money politics going on with the modus operandi of money politics is varied, while the money politics. Election regulations contained in Article 82 paragraph ( 1 ) and ( 2 ) of Act No. 32 of 2004 are legal loopholes of the legal aspects of the subject of money politics just a couple of candidates and/or the campaign team and aspects of legal sanctions no deterrent effect . Article 117 paragraph ( 2 ) of Act No. 32 of 2004 just threatened with imprisonment a minimum of 2 ( two ) months and a maximum of 12 (twelve ) months and / or a fine of Rp . 1,000,000.00 ( one million rupiah ) and maximum Rp . 10,000,000.00 ( ten million dollars ).